Oxford Energy Forum, Special Issue 103 - Bassam Fattouh; Peter Stewart (Oxford Energy Forum: A Quarterly Journal for Debating Energy Issues and Policies, 2015)
Energy trading in Europe is on the verge of a fundamental transformation. The implementation of a host of new regulations: the European Market Infrastructure Regulation (EMIR), the Markets in Financial Instruments Directive (MiFID), the Markets in Financial Instruments Regulation (MiFIR), the Market Abuse Regulation (MAR), the Capital Requirements Regulation (CRR), and the Capital Requirements Directive IV (CRD IV) will have profound implications for how international oil companies, trading houses, brokerage firms, investment banks, price-reporting agencies, and futures exchanges do business. While there is a consensus among the contributors to this Forum that the new regulations will change the landscape by increasing the complexity of the trading business and the cost of compliance, as well as increasing reporting and capital requirements, there remains much uncertainty as to whether these new regulations will achieve their intended objectives. Of particular concern are the unintended consequences of some of these regulations in terms of: reducing market liquidity, reducing the number of market players, the risks of regulatory arbitrage, and increasing the cost of hedging.
Keywords: 330